O alçamento de vogais médias pretônicas e os itens lexicais (Revista de Estudos da Linguagem, 1995)
The main purpose ofthis paper is to make evident tbat many lexical items ofthe portuguese language cannotbe seen as exceptions to the pretonic mid vowels raining rules as they bave been cobsidered and tbat through the residue analysis the remaining exceptions bring out the need ofunderstanding language as "enunciação" in the linguistic change processes.